Vasconcelos, Elaine da Silva. Complexos de íons lantanídeos com carboxilatos aromáticos: dependência das propriedades fotoluminescentes com a natureza e a posição de substituintes elétron-doadores - Vasconcelos, Elaine da Silva (2014)
In the present work, it has been investigated the influence of the position of electron-donor substituents in aromatic carboxylate ligands on the photoluminescent properties of Tb3+ and Eu3+complexes. It was synthesized complexes of general formula [Ln (R-2-Bz)3fen] and [Ln (4-R-Bz)3fen] with Ln = Eu3+, Gd3+ and Tb3+; R =-NH2,-NH (CO) CH3,-OH,-O (CO) CH3,-O (C4H9); phen = 1,10-phenanthroline, which were characterized by complexometric titration, elemental analysis, absorption IR spectra and diffuse reflectance. The phosphorescence spectra of the complexes [Gd (2-R-Bz)3fen] and [Gd (4-R-Bz)3fen] showed that the energies of the triplet states of the ligands are coordinated above and in a good resonance condition with the emitting states of both ions Eu3+ and Tb3+ and it is favorable to the efficient process of ligand-metal energy transfer. Such states are localized on the 1,10-phenanthroline ligands in all complexes. For the complexes of the Tb3+ ion, it was found that acetylation of both substituents N or O-donors caused an increase in the lifetimes for most compounds, which is much higher at ambient temperature than at low temperature. For the Eu3+ complex it was observed a strong dependence of the intensity parameters Ω2 and quantum efficiency of luminescence with the nature and position of the electron-donors substituents, which could be rationalized on the basis of electronic and steric effects. Such effects exerted strong influence on the LMCT charge transfer states, directly contributing to the dependence of the quantum efficiency of luminescence with the position of the electron-donor substituents the carboxylate ligands. Steric interactions promoted conjugation breakage due to the removal of the aromatic ring from the conjugation plane of the carboxylate group, reducing the ability of the electron-donating oxygen atoms and consequently increasing the LMCT energy states. It was demonstrated, for the first time, that the loss of conjugation by steric interaction may eliminate or reduce the effect of LMCT states as a suppression channel of luminescence in Eu3+ complexes.